Tracing The Tracts Of Qaṣaṣ: Towards A Theory Of Narrative Pedagogy In Islamic Education - Muhammad Fawwaz Muhammad Yusoff (Multidisciplinary Digital Publishing Institute, 2024)
Religions Volume 14 Issue 10 Page (1-21)